2017
DOI: 10.1111/jam.13580
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the biosynthesis gene cluster for the novel lantibiotic paenilan fromPaenibacillus polymyxaE681 and characterization of its product

Abstract: Paenibacillus species are a good source of new lantibiotics, and the conservation of the paenilan gene among Paenibacillus sp. implies paenilan has an important function(s) for their survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
(85 reference statements)
4
17
0
Order By: Relevance
“…Analysis of the genome sequence of strain E681 showed that it harbors a class-I lanthipeptide cluster. The antiSMASH results are in agreement with the RefSeq annotation and the analysis of Park et al [ 36 ] (details are given in S.2.3.4.1).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Analysis of the genome sequence of strain E681 showed that it harbors a class-I lanthipeptide cluster. The antiSMASH results are in agreement with the RefSeq annotation and the analysis of Park et al [ 36 ] (details are given in S.2.3.4.1).…”
Section: Resultssupporting
confidence: 88%
“…Analysis of the genome sequence of strain CR1 showed that it harbors a class-I lanthipeptide cluster that codes for a lanthipeptide highly similar to paenilan, which was characterized in [ 36 ]. The nt sequence of the gene coding for the predicted lanthipeptide ( Table S1 ) is 100% identical to ‘X809_RS07820’, which has been annotated on the RefSeq genome as coding for a hypothetical protein (WP_023987834) ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The functions of the putative biosynthetic proteins encoded at the upstream and downstream of the precursor gene were further verified through conserved domain analysis using CD-Search ( Table S4 ). In comparison to the extensively studied paenibacillin, paenilan, and paeninodin produced by Paenibacillus polymyxa OSY-DF (He et al, 2008 ), Paenibacillus polymyxa E681 (Park et al, 2017 ), and Paenibacillus dendritiformis C454 (Zhu et al, 2016 ), respectively, characterization and determination of biosynthesis mechanisms of TOMM and sactipeptide in other Paenibacillus polymyxa received less attention by the researchers. TOMM is featured by the presence of thiazole and oxazole heterocycles derived from modification of cysteine and serine residues (Metelev and Ghilarov, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“… Theoretical isoelectric point and molecular weight of mature peptides (1–5; bold) were computed using Compute pI/MW tool of ExPAsy (Bioinformatics Resource Portal). Cleavage site of paenibacillin, paenilan, and lasso peptide were determined based on previous research (He et al, 2008 ; Zhu et al, 2016 ; Park et al, 2017 ). Cleavage site of sactipeptides and thiazole/oxazole modified microcins were predicted using SignalP 5.0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation